Awareness on smoking cessation counseling among dentists in Kerala, India - Benley George; Vinod Mathew Mulamoottil; Sunu Alice Cherian; Jacob John; T Aby Mathew; Shibu Thomas Sebastian (Wolters Kluwer Medknow Publications, 2015)
Introduction: Although dentists are ideally placed to deliver smoking cessation advice and assistance to their patients, smoking cessation interventions are not often incorporated as a routine part of dental care. Aim: To assess the awareness on smoking cessation counseling among dental practitioners in Kerala. Materials and Methods: A pretested questionnaire was used for the study. Four hundred and sixteen registered dentists practicing all over Kerala participated in the survey. Results: Dentists are willing to ask and advise patients about smoking, but are less inclined to assist patients to quit or arrange follow-up. Dentists are more likely to implement one-off, opportunistic interventions rather than take a systematic preventive approach. Dentists are interested in attending further education and say they require training to be relevant to the context of their day-to-day running of the dental practice. Conclusions: Training should aim to legitimize the dentist's role in smoking cessation and provide strategies and resources so that dentists can practice interventions as part of their day-to-day work.